Pemilihan Green Supplier Berdasarkan Fuzzy AHP Dengan Metode Fuzzy Topsis - Akhmad Ghiffary Budianto (Department Industrial Engineering, University of Muhammadiyah Malang, 2016)
PT. Petrokimia Gresik is a company producing fertilizer with raw material reactive chemicals. In the production process required adjuvant to speed up the process. On the other hand, the company also wants to realize its mission to the environment in accordance with goverment regulations. So that the company’s activities will reach a point of balance between the economy an the environment. The goal of this research is to help the company in determining the criteria and sub-criteria are influential in selecting green suppliers with Fuzzy AHP method, and helping to choose the best alternative green supplier with Fuzzy TOPSIS method. There are 9 criteria and 19 sub-criteria and 4 alternative supplier in this study. Based on the calculation method of Fuzzy AHP, the criteria that affect are the quality and environmental management system, whle for sub criteria are green image and the PPM levels. Based on the calculation method of Fuzzy TOPSIS obtained the best alternative solution for the company is supplier 1 from 4 alternative supplier